Anthropometry of Malaysian young adults - Karuppiah, Karmegam; Salit, Mohd Sapuan; Ismail, Mohd Yusof; Ismail, Napsiah; Mohd Tamrin, Shamsul Bahri; Gobalakrishnan, Mohana Krishnan; Palanimuthu, Seetha; Palaniandy, Thiyagu (Human Ergology Society, 2011)
This paper presents the results of an anthropometric data collected from polytechnic students in Malaysia. A total of 1032 (595 males and 437 females) students participated in the study. Their ages ranged from 18 to 24 years. A total of 34 anthropometric dimensions were measured. Descriptive statistics such as mean, standard deviation, standard error of mean, coefficient of variation, minimum, maximum and percentile for each parameter were estimated. In addition, the comparison between Malaysia anthropometric data and Thailand (South) anthropometric data were also presented. The results show that there is a total of 12 and 11 (of dimensions parameters) significant differences (p < 0.05) between the male and female adults respectively.